2019
DOI: 10.1249/mss.0000000000001837
|View full text |Cite
|
Sign up to set email alerts
|

Time Trial Performance Is Sensitive to Low-Volume Autologous Blood Transfusion

Abstract: Purpose This study tested the hypothesis that autologous blood transfusion (ABT) of ~50% of the red blood cells (RBC) from a standard 450-mL phlebotomy would increase mean power in a cycling time trial. In addition, the study investigated whether further ABT of RBC obtained from another 450-mL phlebotomy would increase repeated cycling sprint ability. Methods In a randomized, double-blind, placebo-controlled crossover design (3-month wash-out), nine hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(54 citation statements)
references
References 25 publications
3
51
0
Order By: Relevance
“…When applying a double-blind, placebo-controlled crossover design and 7–11 weeks cryopreservation, performance was enhanced by ~ 30% in a TTE lasting ~ 10 min [10] and by 3% in 5 mile and 10 km time trials (TT) [9, 14] in well-trained males receiving a reinfusion of RBCs reconstituted to normal haematocrit (Hct) from a ~ 900 mL donation. Generally, the high-quality ABT studies report enhanced performance by ~ 3–5% compared with pre-reinfusion performance in time trials lasting ~ 30–45 min [7, 9, 14] and that TTE is prolonged by ~ 30% in a test lasting ~ 10 min [10]. It is of note that all the best controlled studies investigated well-trained male athletes (Table 1).…”
Section: Effect Of Abt On Human Exercise Performancementioning
confidence: 99%
See 1 more Smart Citation
“…When applying a double-blind, placebo-controlled crossover design and 7–11 weeks cryopreservation, performance was enhanced by ~ 30% in a TTE lasting ~ 10 min [10] and by 3% in 5 mile and 10 km time trials (TT) [9, 14] in well-trained males receiving a reinfusion of RBCs reconstituted to normal haematocrit (Hct) from a ~ 900 mL donation. Generally, the high-quality ABT studies report enhanced performance by ~ 3–5% compared with pre-reinfusion performance in time trials lasting ~ 30–45 min [7, 9, 14] and that TTE is prolonged by ~ 30% in a test lasting ~ 10 min [10]. It is of note that all the best controlled studies investigated well-trained male athletes (Table 1).…”
Section: Effect Of Abt On Human Exercise Performancementioning
confidence: 99%
“…To our knowledge, we recently completed the first study on the effect of a low-volume ABT using a randomized, double-blind, placebo-controlled crossover design. We demonstrated that reinfusion with ~ 135 mL of cold-stored RBCs, corresponding to ~ 225 mL of whole blood, is sufficient to increase mean power by ~ 5% and reduce elapsed time by ~ 4% in a 650 kcal cycling TT [7]. Concomitantly, haemoglobin concentration ([Hb]), Hct, and RBC count increased by 3% compared to their levels 3 days before reinfusion.…”
Section: Effect Of Abt On Human Exercise Performancementioning
confidence: 99%
“…Various strategies exist to artificially increase an athlete's red blood cell mass, several of which are prohibited in sports and, consequently, are commonly referred to as blood doping. Especially the enhanced arterial oxygen concentration resulting from an increased number of erythrocytes was identified as a key factor positively affecting endurance performance, and also chronically altitude‐adapted endurance athletes were reported to respond to drug‐induced erythropoiesis with an enhanced hematocrit, hemoglobin concentration, reticulocyte percentage, and improved time trial performances …”
Section: Manipulation Of Blood and Blood Componentsmentioning
confidence: 99%
“…Also, very few studies have investigated the effects of low-volume blood transfusions on athletic performance, and these results are controversial. 24,25 The considerable amount of doping cases (Table 2) coinciding with implementation of the ABP provides grounds to speculate that the magnitude of the performance decrease reflects the gains that were available by means of blood doping before. Such performance increases would require transfusion of >800 mL of whole blood or the use of erythropoiesis-stimulating substances in significant dosages, both of which are reliably detectable by the ABP nowadays.…”
Section: Changes In Performancementioning
confidence: 99%